Avetik Isahakyan’s “Agha Nazar” Tale and its Western Armenian Reception - Makaryan, Albert (Bulletin of Yerevan University B: Philology, 2026)
In the context of the Brothers Grimm’s Brave Tailor, the Greek Mr. Lazarus, the Russian Foma Berennikov and other literary adaptations of the eternal and famous hero type that is widely spread in world literature, the Armenian versions of Brave Nazar, too, have long had their rightful place. Literary developments of this theme are diverse in terms of genre: prose or verse fairy tales, comedy, novels, etc. In Armenian literature it was developed by the classics such as Hovhannes Tumanyan, Avetik Isahakyan, Derenik Demirchyan, Stepan Zoryan, Hamastegh, and among the modern ones are Mkrtich Sargsyan, Hovhannes Grigoryan and Norayr Adalyan... Many valuable studies have been written about these developments by examining them from different perspectives. This paper, however, is dedicated to a work that is still unknown to our reader: it is the fairy tale in verse "Hanum Nazar" by one of the prominent Western Armenian woman of letters Sipil. Up to now only some hints have been made about it but no reference was done to the original source. "Hanum Nazar", by the way, is noteworthy in several aspects . First of all, it was written under the direct influence of Avetik Isahakyan’s "Agha Nazar" and is dedicated to Isahakyan himself. Beside, to some extent, it has become its literary parody. Let us note that such a tradition already existed in Armenian literature: it is worth mentioning, for example, the novel-parody "From the Memoirs of an Executive" written by Shirvanzadeh on the occasion of Raffi’s "The Golden Rooster" that is dedicated to Raffi’s literary anniversary. The primary objectives of our study were to examine, using a comparative method, the plot and compositional similarities and differences between "Agha Nazar" and "Hanum Nazar", and Sipil’s deliberate alternation of male/female heroes, which gives the work a completely new tone, making it more intriguing and fascinating. Our important conclusion here is that both authors, albeit in different ways but by their own means have managed to reveal the universal and eternal nature of the vicious phenomenon. Besides, by enthroning the heroine for the first time in "Hanum Nazar", the author also responds to the issue of the so-called "emancipation" of women, ironically presenting the fate of a lazy and undeserving woman who, by a stroke of luck, achieved fame.